PKM SMU PLUS MIFTAHUL ULUM “OPTIMALISASI EDUKASI GENDER DAN SEKSUALITAS MELALUI PENDAMPINGAN RECARE - Dian Permatasari; Emdat Suprayitno; Rasyidah Rasyidah (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: Teenagers have a high level of curiosity and will look for something new about sexuality, but they do not understand sexuality and gender issues. The incidence of gender inequality in adolescents is due to unhealthy associations (toxic relationships) and a negative understanding of sexuality, which is still lacking, as evidenced by the number of pregnancies outside of marriage. The purpose of this study is to increase adolescents' understanding and knowledge about gender and sexuality. Methods: The method in this service is to establish Recare (adolescent care), after which assistance is provided in the form of education, discussion, and evaluation. This activity is carried out by teenagers who care about other teenagers and want to help them overcome their problems regarding gender and sexuality. The analysis in the study was carried out by giving treatment and then evaluating it before and after being given education. Results: The results of the evaluation showed that there was an increase in the knowledge of adolescents at SMU Plus Miftahul Ulum based on the results of statistical tests (p-value = 0.000). Thus, it can be concluded that the indicators of the success of this community service program have been achieved and proven by a change in the participant's level of knowledge. Conclusion: Similar activities need to be carried out regularly and continuously in order to minimize problems in the lives of adolescents in the future, especially in efforts to prepare family life for adolescents.